AN APPLICATION PUZZLE 31 GAME ON LOCAL AREA NETWORK (LAN) - Rizky Trianda; Arpan; Zulfahmi Syahputra (Sean Institute, 2022)
Puzzle Game 31 is a numbers game played on a 6 x 4 square, where each column contains numbers from 1 to 6 such that the first row contains the value of all one, the second line contains the value of two all and so on. The first player will start selecting a number in the box and mark it so that it cannot be used again. All values ​​taken will be added up. The goal of the game is to score 31 points, which means that the player who reaches 31 first wins the game. This game is usually played by two players.